Caspase-3 Inhibition Attenuates the Cytopathic Effects of EV71 Infection - Song, Fengmei; Yu, Xiaoyan; Zhong, Ting; Wang, Zengyan; Meng, Xiangling; Li, Zhaolong; Zhang, Shuxia; Huo, Wenbo; Liu, Xin; Zhang, Yahong; Zhang, Wenyan; Yu, Jinghua (Frontiers in Microbiology, 2018)
Previous studies demonstrate that human enterovirus 71 (EV71), a primary causative agent for hand, foot, and mouth disease, activates caspase-3 through the non-structural viral 3C protein to induce host cell apoptosis; however, until now it was unclear how 3C activates caspase-3 and how caspase-3 activation affects viral production. Our results demonstrate that 3C binds caspase-8 and caspase-9 but does not directly bind caspase-3 to activate them, and that the proteolytic activity of 3C is required by the activation of caspase-8, caspase-9 and caspase-3. Inhibition of caspase-3 activity attenuates apoptosis in 3C-transfected cells. Furthermore, caspase-3 inhibitor protects host cells from the cytopathic effect of EV71 infection and prevents cell cycle arrest, which is known to be favored for EV71 viral replication. Inhibition of caspase-3 activity decreases EV71 viral protein expression and viral production, but has no effect on viral entry, replication, even polyprotein translation. Therefore, caspase-3 is exploited functionally by EV71 to facilitate its production, which suggests a novel therapeutic approach for the treatment and prevention of hand, foot, and mouth disease.